Heavy-load ultralow-friction multilayer composite coating on rubber surface and preparation method of heavy-load ultralow-friction multilayer composite coating
By forming a reinforcement layer on the rubber surface, depositing metal carbide layer and gradient transition layer, and spraying MXene-based two-dimensional material, the wear problem caused by friction heat of rubber seals under heavy load conditions is solved, and ultra-low friction characteristics are achieved. High binding strength, suitable for large-area industrial applications.
Patent Information
- Application Number
- CN202411427358.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
AI Technical Summary
Rubber seals have rapid wear and failure due to friction heat under high pressure conditions, and it is difficult for the prior art to achieve ultra-low friction characteristics under heavy load conditions.
The reinforcement layer is formed on the rubber surface by in-situ ion co-injection method, the metal carbide layer and the gradient transition layer are deposited, and the MXene-based two-dimensional material nanosheets are sprayed on the surface of the amorphous carbon film to form a multi-layer composite coating to achieve high bonding With strength and high bearing capacity, the amorphous carbon film is transformed into a graphene-like structure to achieve ultra-low friction characteristics.
The friction coefficient of the rubber surface is significantly reduced, the bonding strength and load bearing capacity are improved, and the long-term ultra-low friction characteristics under heavy load conditions are achieved, which solves the problem of wear and failure of rubber seals.
Smart Images

Figure CN119241894A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heavy-load ultra-low friction multilayer composite coating on a rubber surface and a preparation method thereof, and in particular to a preparation method of a multilayer composite coating through surface in-situ ion co-injection, multilayer composite gradient layers, carbon films and MXene-based two-dimensional material, and belongs to the field of solid lubricating materials and tribology. Background Art
[0002] There are a large number of sealing devices in modern industrial equipment to prevent leakage of working media and intrusion of external dust and foreign objects. Once the sealing medium leaks, it may cause material loss and equipment damage at the least, or even cause fire and explosion. Most dynamic seal leakage accidents are related to the sealing failure of the seal. Rubber has excellent properties such as good elastic recovery and pressure resistance, and is the most commonly used sealing material. However, after the rubber dynamic seal is installed in the sealing groove, it is squeezed and deformed by the high-pressure medium, and the friction coefficient with the steel groove wall and the sealing rod under the action of periodic stress is extremely high (µ>1). The friction heat generated by high friction can easily cause the rubber seal to soften and quickly wear out and fail, causing the high-pressure sealing medium to leak from the damaged part, thereby affecting the safe and reliable service of the equipment. Therefore, solving the problem of wear and failure of rubber seals must start with reducing friction.
[0003] Carbon film has excellent properties such as low adhesion to steel, low deposition temperature (deposition temperature ≤ 100℃, which will not cause fatal damage to the nitrile rubber matrix), controllable composition and mechanical strength, variable structure (such as multi-micro-nano structure, multi-element doping, etc.), and low friction and wear. Therefore, it is an ideal coating for achieving low friction on rubber surfaces. However, as the working conditions of rubber dynamic seals become more and more demanding, that is, most rubber dynamic seals are required to serve stably and reliably under heavy load conditions, but it is still facing great challenges to achieve ultra-low friction on rubber surfaces under heavy load conditions. At the same time, the rubber material is a soft substrate, while the carbon film is a hard film. Ensuring that the hard film on the soft surface will not be mechanically fragmented under heavy load (high load-bearing capacity) and will not be peeled off along the tangential direction (high bonding characteristics) to form a hard abrasive three-body is the key factor to achieve ultra-low friction on the rubber surface. Therefore, how to design and prepare a high-bonding and high-load multi-layer composite coating and achieve its heavy-load ultra-low friction characteristics is the top priority to solve the wear failure of rubber seals in the future. Summary of the invention
[0004] The purpose of the present invention is to provide a heavy-load ultra-low friction multilayer composite coating on a rubber surface and a preparation method thereof, wherein the surface of the rubber substrate is strengthened by in-situ ion co-injection, and the high binding and high load-bearing characteristics of the amorphous carbon film on the rubber surface are achieved through metal carbide + gradient transition layer, and finally MXene-based two-dimensional material nanosheets are sprayed, which can act as a "template" under heavy-load conditions to continuously transform the amorphous carbon film wear debris into a graphene-like structure in situ, and form a heterojunction pair with it in situ, thereby achieving the ultra-low friction characteristics of the multilayer composite coating under heavy-load conditions.
[0005] 1. Heavy-load ultra-low friction multi-layer composite coating on rubber surface and preparation method thereof The heavy-loaded ultra-low friction multi-layer composite coating on the rubber surface of the present invention is firstly prepared by co-injecting metal and carbon elements into the rubber surface by an in-situ ion co-injection method to form a reinforcement layer, and then depositing a metal carbide layer, a gradient transition layer and an amorphous carbon film in sequence on the reinforced rubber surface, and finally spraying MXene-based two-dimensional material nanosheets on the surface of the amorphous carbon film to obtain a heavy-loaded ultra-low friction multi-layer composite coating on the rubber surface.
[0006] The method for preparing the heavy-load ultra-low friction multi-layer composite coating on the rubber surface comprises the following steps: 1) Rubber base cleaning: Cut the rubber sheet into 20×20mm 2 The rubber sheet is soaked in a 50~60℃ soapy water solution for ultrasonic cleaning for 30~60 minutes to remove grease and dirt on the rubber surface; then it is taken out and soaked in 90~95℃ distilled water for ultrasonic cleaning for 20~30 minutes to remove possible residual soapy water solution; finally, it is blown dry with dry nitrogen and placed in a drying oven at 100~120℃ for another 10~20 minutes to evaporate the residual moisture on the rubber surface; the above process is repeated 4~5 times; The rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, silicone rubber and EPDM rubber, the rubber surface roughness is ≤200nm, and the rubber thickness is 2-4mm.
[0007] 2) In-situ co-injection of metal and carbon elements on the rubber substrate surface: The cleaned rubber substrate is placed in a magnetron sputtering vacuum chamber integrated with a Mevva-V.Ru vacuum arc ion source and evacuated to ≤1×10 -6 Pa; adjust the carbon target current to 45~60A, duty cycle to 40~50%, beam density to 0.48~0.64A / 100cm 2 ·s; at the same time, adjust the metal target current to 20A~40A, the duty cycle to 50%, and the beam density to 0.3A~0.42A / 100cm 2 ·s, total injection time is 0.5~2h; control acceleration voltage -20~-30kV, frequency 1~3 Hz; The implanted metal target material is selected from one of Ti, Cr and W targets, and the carbon target material is selected from graphite target. The implanted strengthening layer has a depth of 300-1200 nm, and the ion concentration of the implanted layer changes gradually and decreases with the depth of the layer.
[0008] 3) Deposition of metal carbide layer: high-power micro-pulse magnetron sputtering technology is used to deposit a metal carbide layer on the surface of the rubber substrate as a bearing layer; specific deposition process: the metal target material is selected from one of W, Cr, and Ti, 45~60sccm argon and 60~90sccm methane are introduced, the target peak current is adjusted to 150A~200A, the substrate bias is -500~-700V, the gas pressure is maintained between 0.5~0.8Pa, and the deposition time is 30~40 minutes; The metal target material in the metal carbide layer is selected from one of Ti, Cr and W targets, and corresponds to the metal element injected in step 2); the thickness of the metal carbide layer is 1.0-1.2µm.
[0009] 4) Deposition of gradient transition layer: During the above deposition process, the methane flow rate was gradually reduced at a rate of 5 sccm / 5 min, and at the same time, the metal target current was reduced at a rate of 5 A / min until it reached 0 A, and the metal target power supply was turned off; The gradient transition layer is a transition layer in which the metal concentration gradually decreases and the carbon element concentration gradually increases to be consistent with the amorphous carbon film.
[0010] 5) Deposition of amorphous carbon film: turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8-12 cm, the target current to 3 A, the argon flow rate to 45-60 sccm, the Ar / CH4 flow ratio to 1.5:1, the substrate negative bias voltage to 700 V, the gas pressure to 0.5-0.8 Pa, the duty cycle to 40-45%, the frequency to 60-70 KHz, and the deposition time to 120-150 min; the amorphous carbon film is a hydrogenated amorphous carbon film with a film thickness of 500 nm to 1.0 µm.
[0011] 6) Spraying MXene two-dimensional material layer: dissolving MXene two-dimensional material nanosheets in a volatile solvent and loading them into a portable sprayer, and using the sprayer to evenly spray them onto the surface of the amorphous carbon film, and after the solvent is completely volatilized, the multilayer composite coating of the present invention can be obtained. The MXene two-dimensional material is one or more of Ti-based, V-based, and Mo-based MXene two-dimensional materials, and the volatile solvent is one of ethanol and acetone.
[0012] Figure 1This is a schematic diagram of the cross-sectional structure of the heavy-load ultra-low friction multilayer composite coating on the rubber surface prepared by the present invention. It can be seen that the surface of the in-situ ion co-injection is both a strengthening layer and an in-situ bearing layer; at the same time, a metal carbide ceramic layer corresponding to the co-injection element is deposited on the surface of the co-injection strengthening layer to further improve the coating's bearing capacity; in addition, a gradient transition layer is designed between the metal carbide layer and the amorphous carbon film, which can further improve the coating's bonding strength and weaken the risk of interface peeling caused by the increase in the number of layers; finally, MXene-based two-dimensional material nanosheets are sprayed on the surface of the amorphous carbon film, which can be used as a "template" to directional cut the amorphous carbon film debris under heavy load conditions and continuously transform it into a graphene-like structure, and form a heterojunction pair with it in situ to achieve its ultra-low friction characteristics. The present invention effectively breaks through the technical bottleneck that the current hard carbon-based coating on the soft surface of rubber is difficult to achieve ultra-low friction under heavy load, and the process is easy to control and has strong operability. The obtained multilayer composite coating on the rubber surface has ultra-low friction characteristics under heavy load conditions and is easy to be applied industrially on a large scale.
[0013] 2. Performance test of multi-layer composite coating on rubber surface 1. Bonding strength The X-cut method was used to test the bonding strength between the coating and the rubber substrate. The results showed that the bonding strength reached 5A level (the highest level in the industry), indicating that the coating has high bonding strength.
[0014] 2. Friction coefficient Figure 2 The friction coefficient curve of the heavy-load ultra-low friction rubber surface multilayer composite coating prepared by the present invention. The tribological performance of the rubber surface multilayer composite coating of the present invention was evaluated by a friction and wear tester. The friction conditions were: ball-disc rotation, normal load 40N, friction pair φ6mm GCr15 steel ball, and test environment was air. The results showed that the friction coefficient of conventional pure carbon film was high (~0.61), while the friction coefficient of the multilayer composite coating of the present invention was significantly reduced (0.02~0.05).
[0015] In summary, the present invention has the following advantages compared with the prior art: 1. In-situ ion co-injection is used to form a surface strengthening layer, and a metal carbide ceramic layer corresponding to the co-injection element is deposited on the surface of the co-injection strengthening layer to further improve the bearing capacity of the coating; 2. A gradient transition layer is designed between the metal carbide layer and the amorphous carbon film, which can further improve the film bonding strength and weaken the risk of interface peeling caused by the increase in the number of coating layers; 3. The outermost layer of the multi-layer composite coating designed by the present invention is a MXene-based two-dimensional material layer, which has excellent mechanical strength and wear resistance. Especially under heavy load conditions, the MXene-based two-dimensional material can act as a "template" to directionally shear the amorphous carbon film wear debris, and continuously transform it into a graphene-like structure, and form a heterojunction with it in situ, thereby achieving long-term ultra-low friction characteristics of the composite coating. In addition, the MXene-based two-dimensional material layer adopts a simple spraying technology, which is easily transferred to the steel dual surface during the friction process, thereby achieving long-term lubrication; 4. The process of the present invention is simple and easy to control, and has strong operability. The obtained multi-layer composite coating on the rubber surface has ultra-low friction characteristics under heavy load conditions and is easy to realize large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of the cross-sectional structure of the heavy-loaded ultra-low friction multi-layer composite coating on the rubber surface of the present invention.
[0017] Figure 2 This is a friction coefficient curve of the multi-layer composite coating prepared by the present invention and a single-layer carbon film on the rubber surface. DETAILED DESCRIPTION
[0018] The preparation method and performance of the heavy-load ultra-low friction multi-layer composite coating on the rubber surface of the present invention are further described below through specific examples.
[0019] Example 1 (1) Cut a 300×300×2 mm black nitrile rubber sheet (surface finish Ra<200 nm, thickness 3 mm) into 20×20 mm 2 The rubber sheet was soaked in 60℃ soapy water for 30 minutes to remove grease and dirt on the rubber surface; then it was taken out and soaked in 90℃ distilled water for 30 minutes to remove possible residual soapy water solution; finally, it was blown dry with dry nitrogen and placed in a drying oven at 120℃ for another 20 minutes to completely evaporate the residual water on the rubber surface. The above process was repeated 5 times.
[0020] (2) Place the cleaned rubber substrate in a magnetron sputtering vacuum chamber integrated with a Mevva-V.Ru vacuum arc ion source (a Ti target and a graphite target are pre-installed in the vacuum chamber as co-injection ion sources), close the vacuum chamber door, and evacuate the vacuum to ≤1.0×10 –6 Pa; turn on the DC pulse arc power supply, adjust the carbon target current to 45A, the duty cycle to 40%, and the beam density to 0.48A / 100cm 2 ·s. At the same time, the Ti metal target current was adjusted to 20A, the duty cycle was 50%, and the beam density was 0.42A / 100cm 2·s, injection time was 0.5 h; acceleration voltage was controlled at -20 kV, frequency was 1 Hz.
[0021] (3) Turn off the arc ion source power supply, turn on the high-power micro-pulse magnetron sputtering power supply, select a metal Ti target, pass 45 sccm argon and 60 sccm methane, adjust the peak current to 150 A, the substrate negative bias voltage to 500 V, maintain the gas pressure at about 0.5 Pa, and deposit for 30 minutes.
[0022] (4) After the above deposition is completed, the methane flow rate is gradually reduced at a rate of 5 sccm / 5 min, and the metal target current is reduced at a rate of 5 A / min until it reaches 0 A.
[0023] (5) Turn off the high-power micro-pulse magnetron sputtering power supply, turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8 cm, the target current to 3 A, the argon flow rate to 45 sccm, the CH4 flow rate to 30 sccm, the substrate negative bias voltage to 700 V, the gas pressure to 0.5 Pa, the duty cycle to 40%, the frequency to 60 KHz, and the deposition time to 120 min. After the deposition is completed, wait for the temperature in the vacuum chamber to cool to room temperature before taking out the sample.
[0024] (6) The Ti3C2MXene two-dimensional material nanosheets are dissolved in anhydrous ethanol solvent and loaded into a portable sprayer, and the nanosheets are evenly sprayed onto the surface of the amorphous carbon film by the sprayer, and the multilayer composite coating of the present invention can be obtained after the solvent is completely evaporated. The bonding strength of the multilayer composite coating on the surface of the nitrile rubber is 5A grade, and the friction coefficient is 0.02 under a heavy load of 40N.
[0025] Example 2 (1) The silicone rubber pre-cleaning step is the same as in Example 1. Wherein: the silicone rubber surface finish Ra is less than 200 nm, and the thickness is 3 mm.
[0026] (2) Place the cleaned rubber substrate in a magnetron sputtering vacuum chamber integrated with a Mevva-V.Ru vacuum arc ion source (Cr target and graphite target are pre-installed in the vacuum chamber as co-implanted ion materials), close the vacuum chamber door, and evacuate the vacuum to ≤1.0×10 –6 Pa; turn on the DC pulse arc power supply, adjust the carbon target current to 60A, the duty cycle to 50%, and the beam density to 0.64A / 100cm 2 ·s. At the same time, the Cr metal target current was adjusted to 30A, the duty cycle was 50%, and the beam density was 0.30A / 100cm 2 ·s, injection time was 1.5 hours; acceleration voltage was controlled at -30 kV, frequency was 3 Hz.
[0027] (3) Turn off the arc ion source power supply, turn on the high-power micro-pulse magnetron sputtering power supply, select a metal Cr target, pass 60 sccm argon and 90 sccm methane, adjust the peak current to 200 A, the substrate negative bias voltage to 700 V, keep the gas pressure at about 0.8 Pa, and deposit for 40 minutes.
[0028] (4) After the above deposition is completed, the methane flow rate is gradually reduced at a rate of 5 sccm / 5 min, and the metal target current is reduced at a rate of 5 A / min until it reaches 0 A.
[0029] (5) Turn off the high-power micro-pulse magnetron sputtering power supply, turn on the graphite target sputtering power supply, adjust the target-substrate distance to 12 cm, the target current to 3 A, the argon flow rate to 60 sccm, the CH4 flow rate to 40 sccm, the substrate negative bias voltage to 700 V, the gas pressure to 0.8 Pa, the duty cycle to 45%, the frequency to 70 KHz, and the deposition time to 150 min. After the deposition is completed, wait for the temperature in the vacuum chamber to cool to room temperature before taking out the sample.
[0030] (6) The V4C3MXene two-dimensional material nanosheets are dissolved in an acetone solvent and loaded into a portable sprayer, and the nanosheets are evenly sprayed onto the surface of the amorphous carbon film by the sprayer, and the multilayer composite coating of the present invention is obtained after the solvent is completely evaporated. The multilayer composite coating on the surface of the silicone rubber has a bonding strength of 5A grade, and its friction coefficient is 0.05 under a heavy load of 50N.
[0031] Example 3 (1) The hydrogenated nitrile rubber pre-cleaning step is the same as in Example 1. Wherein: the silicone rubber surface finish Ra is less than 200 nm, and the thickness is 2 mm.
[0032] (2) A metal W target is selected as the metal ion implantation source, and other parameters are the same as those in Example 2.
[0033] (3) Turn off the arc ion source power supply, turn on the high-power micro-pulse magnetron sputtering power supply, select a metal W target, pass 50 sccm argon and 75 sccm methane, adjust the peak current to 175 A, adjust the substrate negative bias to 600 V, maintain the gas pressure at ~0.8 Pa, and deposit for 40 minutes.
[0034] (4) After the above deposition is completed, the methane flow rate is gradually reduced at a rate of 5 sccm / 5 min, and the metal target current is reduced at a rate of 5 A / min until it reaches 0 A.
[0035] (5) Turn off the high-power micro-pulse magnetron sputtering power supply, turn on the graphite target sputtering power supply, adjust the target-substrate distance to 10 cm, the target current to 3 A, the argon flow rate to 60 sccm, the CH4 flow rate to 40 sccm, the substrate negative bias voltage to 700 V, the gas pressure to about 0.8 Pa, the duty cycle to 40%, the frequency to 60 KHz, and the deposition time to 135 min. After the deposition is completed, wait for the temperature in the vacuum chamber to cool to room temperature before taking out the sample.
[0036] (6) The Mo2C MXene two-dimensional material nanosheet is fully dissolved in an acetone solvent and loaded into a portable sprayer, and the nanosheet is evenly sprayed onto the surface of the amorphous carbon film by the sprayer, and the multilayer composite coating of the present invention is obtained after the solvent is completely volatilized. The bonding strength of the multilayer composite coating on the surface of the hydrogenated nitrile rubber is 5A grade, and the friction coefficient is 0.04 under a heavy load of 45N.
Claims
1. A heavy-load ultra-low friction multi-layer composite coating on a rubber surface is firstly prepared by co-injecting metal and carbon elements into the rubber surface by an in-situ ion co-injection method to form a reinforcement layer, then depositing a metal carbide layer, a gradient transition layer and an amorphous carbon film in sequence on the reinforced rubber surface, and finally spraying a MXene-based two-dimensional material layer on the surface of the amorphous carbon film to obtain the coating.
2. A method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 1, characterized in that: The following steps are involved: 1) Rubber base cleaning: Cut the rubber sheet into 20×20mm 2 The rubber sheet is soaked in a 50~60℃ soapy water solution for ultrasonic cleaning for 30~60 minutes to remove grease and dirt on the rubber surface; then it is taken out and soaked in 90~95℃ distilled water for ultrasonic cleaning for 20~30 minutes to remove possible residual soapy water solution; finally, it is blown dry with dry nitrogen and placed in a drying oven at 100~120℃ for another 10~20 minutes to evaporate the residual moisture on the rubber surface; the above process is repeated 4~5 times; 2) In-situ co-injection of metal and carbon elements on the rubber substrate surface: The cleaned rubber substrate is placed in a magnetron sputtering vacuum chamber integrated with a Mevva-V.Ru vacuum arc ion source and evacuated to ≤1×10 -6 Pa; adjust the carbon target current to 45~60A, duty cycle to 40~50%, beam density to 0.48~0.64A / 100cm 2 ·s; at the same time, adjust the metal target current to 20A~40A, the duty cycle to 50%, and the beam density to 0.3A~0.42A / 100cm 2 ·s, total injection time is 0.5~2h; control acceleration voltage -20~-30kV, frequency 1~3Hz; 3) Deposition of metal carbide layer: high-power micro-pulse magnetron sputtering technology is used to deposit a metal carbide layer on the surface of the rubber substrate as a bearing layer; specific deposition process: the metal target material is selected from one of W, Cr, and Ti, 45~60sccm argon and 60~90sccm methane are introduced, the target peak current is adjusted to 150A~200A, the substrate bias is -500~-700V, the gas pressure is maintained between 0.5~0.8Pa, and the deposition time is 30~40 minutes; 4) Deposition of gradient transition layer: During the above deposition process, the methane flow rate was gradually reduced at a rate of 5 sccm / 5 min, and at the same time, the metal target current was reduced at a rate of 5 A / min until it reached 0 A, and the metal target power supply was turned off; 5) Deposition of amorphous carbon film: turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8-12 cm, the target current to 3 A, the argon flow rate to 45-60 sccm, the Ar / CH4 flow ratio to 1.5:1, the substrate negative bias voltage to 700 V, the gas pressure to 0.5-0.8 Pa, the duty cycle to 40-45%, the frequency to 60-70 KHz, and the deposition time to 120-150 min; 6) Spraying MXene two-dimensional material layer: dissolving MXene two-dimensional material nanosheets in a volatile solvent and loading them into a portable sprayer, and using the sprayer to evenly spray them onto the surface of the amorphous carbon film. After the solvent is completely evaporated, the multilayer composite coating of the present invention can be obtained.
3. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 1), the rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, silicone rubber and EPDM rubber, the rubber surface roughness is ≤200nm, and the rubber thickness is 2-4mm.
4. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 2), the injection metal target material is selected from one of Ti, Cr, and W targets, and the carbon target material is selected from graphite target.
5. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 2), the depth of the implantation strengthening layer is 300-1200 nm, and the ion concentration of the implantation layer changes gradually and decreases with the layer depth.
6. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 3), the metal target material in the metal carbide layer is selected from one of Ti, Cr, and W targets, and corresponds to the metal element injected in step 2); the thickness of the metal carbide layer is 1.0~1.2µm.
7. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 4), the gradient transition layer is a transition layer in which the metal concentration gradually decreases and the carbon element concentration gradually increases to be consistent with the amorphous carbon film.
8. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 5), the amorphous carbon film is a hydrogenated amorphous carbon film, and the film thickness is 500nm~1.0µm.
9. The method for preparing a heavy-load ultra-low friction multi-layer composite coating on a rubber surface as claimed in claim 2, characterized in that: In step 6), the MXene two-dimensional material is one or more of Ti-based, V-based, and Mo-based MXene two-dimensional materials, and the volatile solvent is one of ethanol and acetone.
Citation Information
Patent Citations
Ultra-hard carbon film and preparation method thereof
CN101554790A
A wear-resistant coating for ordinary carbon steel moving friction pairs in automobiles
CN102286726A
Construction method of ultralow-friction carbon-based composite film on rubber surface
CN113201713A
Method for constructing high-bearing and low-friction rubber surface through in-situ ion co-implantation
CN113201720A
Rubber surface high-bonding ultralow-friction ultrahigh-wear-resistance carbon-based composite coating and construction method thereof
CN117551299A
